2003
DOI: 10.1128/cdli.10.4.552-557.2003
|View full text |Cite
|
Sign up to set email alerts
|

Antigen Capture Enzyme-Linked Immunosorbent Assay for Specific Detection of Reston Ebola Virus Nucleoprotein

Abstract: Antigen capture enzyme-linked immunosorbent assay (ELISA) is one of the most useful methods to detect Ebola virus rapidly. We previously developed an antigen capture ELISA using a monoclonal antibody (MAb), 3-3D, which reacted not only to the nucleoprotein (NP) of Zaire Ebola virus (EBO-Z) but also to the NPs of Sudan (EBO-S) and Reston Ebola (EBO-R) viruses. In this study, we developed antigen capture ELISAs using two novel MAbs, Res2-6C8 and Res2-1D8, specific to the NP of EBO-R. Res2-6C8 and Res2-1D8 recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 33 publications
0
20
0
1
Order By: Relevance
“…It has been demonstrated that the C-terminal half of the filovirus NP has strong antigenicity (Saijo et al, 2001). Multiple studies have identified conformational and linear epitopes for antibodies in this NP region for several viruses within the genus Ebolavirus (Ikegami et al, 2003; Niikura et al, 2001, 2003). …”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the C-terminal half of the filovirus NP has strong antigenicity (Saijo et al, 2001). Multiple studies have identified conformational and linear epitopes for antibodies in this NP region for several viruses within the genus Ebolavirus (Ikegami et al, 2003; Niikura et al, 2001, 2003). …”
Section: Introductionmentioning
confidence: 99%
“…All anti-Zaire sdAb except C exhibit cross-reactivity with Ivory Coast, and all except sdAb A react with Bundibugyo. Overall therefore, Ebolavirus NP comprises a mix of specific and cross-reactive epitopes as seen for a human Fab derived from a survivor of the Zaire Kikwit 1995 outbreak from repertoire cloning and phage display selection on gamma-irradiated virus [63], and mouse monoclonal antibodies generated via hybridomas from mice immunized with recombinant NP [64], [65], [66].…”
Section: Resultsmentioning
confidence: 99%
“…This made the preparation of a mixture of monoclonal antibodies with different specificities necessary. Two novel monoclonal antibodies, Res2-6C8 and Res2-1D8, specific to the nucleoprotein of EBOV-R partly solved the problem [11] .…”
Section: Elisa Assaymentioning
confidence: 99%